Acute psychoactve substance intoxication as practical family doctor’s problem - Drobnik, Leon; Susło, Robert; Trnka, Jakub (Przewodnik Lekarza/Guide for GPs, 2010)
Family doctor has in his practice more and more often cases of acute psychoactive substances intoxications. Considering that in such cases the key role plays fast establishing of correct diagnosis and patients organisms life support, medical practitioners need not only to know the signs and symptoms of intoxications with various substances, but also their colloquial names and possible ways of administering. Proper documenting a psychoactive substance intoxication case and securing specimens for toxicological evaluation are also precious medical practitioners skills to enable those to serve as proofs in possible court trial.